Perceptions of Preparedness for Interprofessional Practice: A Survey of Health Professional Students at Three Universities - Alexa M. Sevin; Maria C. Pruchnicki; Timothy R. Ulbrich; Sarah E. Adkins; Michelle A. Maguire; Christopher G. Green; Nicole V. Brown (University of Minnesota Libraries Publishing, 2015)
Objective: The purpose of this study was to evaluate health professions students' understanding of their own and others' roles on interprofessional (IP) teams, assess students' perceptions of their preparedness to practice in an IP team, and determine differences by type of learning institution and participation in interprofessional education (IPE). Methods: Medical, nursing, and pharmacy students at three Ohio universities with unique IP learning models were surveyed. Descriptive statistics, analysis of variance (ANOVA), chi-square, and two sample t- tests were used to compare measures of knowledge, IPE participation, and preparedness. Results: Of the 981 invited students, 273 completed the survey (27.8% response). Overall, 70.7% of participants felt prepared to work on an IP team. Those who reported participation in IPE were more likely to feel prepared to practice on an IP team compared to those who did not (76.8% [149/194] vs. 55.3% [42/76], p=0.0005). Participation in IPE did not significantly affect knowledge scores (participators 79.6% vs. non-participators 81.0%, p=0.1731). Those who had higher profession-specific knowledge scores were more likely to feel prepared to work with that specific profession. Conclusions: Participation in IPE activities in the representative institutions was high, as was knowledge of professional roles. Both participation in IPE and increased knowledge of roles were associated with increased student-assessed preparedness. Advancement of skills and behaviors including knowledge of roles and other competencies may all be important. Pharmacy in particular should prioritize IPE as a means to elucidate our role on the patient care team.   Type: Original Research